Do We Underestimate the Benefits of Cultural Competition? - Caplan, Bryan; Cowen, Tyler (American Economic Review, 2004)
Economic globalization has drawn fresh attention to cultural issues. The Uruguay Round of trade negotiations debated whether there should be a protectionist “cultural exception” for television and movies, as practiced by the French, Canadians, Brazilians, South Koreans, and Chinese to varying degrees. Governments around the world subsidize culture, in part to favor one national tradition over potential competitors. More generally, cultural questions are central to broader critiques of trade and globalization (Cowen, 2002). Current analyses, however, have neglected some insights from economics. We will suggest that market competition across cultures is desirable and favors relevant notions of diversity. An underlying theme is that individuals hold unjustified prejudices—or, in economic jargon, “systematically biased beliefs”—about globalization.